Urgensi Pelaksanaan Audit Vouching Atas Akun Beban Operasional Perusahaan - Dwi Selvi Amalia; Munari Munari (AKUNTANSI 45, 2024)
This research analyzes the implementation of vouching audits on company operational expense accounts to ensure the validity, accuracy and compliance of financial transactions carried out by a company during a certain period. Reliable financial reports are very important for decision making by investors, creditors and company management. Audits by independent parties are needed to assess the fairness of financial reports, prevent and detect errors and fraud. In the world of business and finance, vouching audits are an important approach to ensuring the validity and accuracy of transactions recorded in a company's operational expense accounts. This article will dig deeper into the implementation of Vouching audits with a focus on the application of interview research methods, observation and documentation analysis. The results show that a vouching audit of operational expense accounts is very important in identifying recording discrepancies, lack of supporting documents, double payments, and expenditures that are not in accordance with policy. The quality and completeness of supporting documents greatly influences the effectiveness of the vouching audit, because this evidence will be the main basis for verifying transactions. This research emphasizes the importance of implementing vouching audits to ensure the validity of financial reports and assist stakeholders in making the right decisions.